Encapsulated sodium butyrate without or with a botanical extract for transitioning neonatal calves - Ting Liu; David P. Casper (Journal of Dairy Science)
ABSTRACT: Butyrate (C4) is known to enhance ruminal papillae development for transitioning neonatal calves from liquid to dry feed, and botanical extracts (BE) have demonstrated enhanced DMI and improved gut health. The hypothesis was that these additives, based on their mechanism of action, could be synergistic to neonatal calf growth performance by improving ruminal function for transitioning from liquid milk replacer (MR) to dry calf starter (CS). Eighty 2- to 5-d old Holstein bull calves were randomly assigned to 1 of 4 treatments using a randomized complete block design with a 2 × 2 factorial treatment arrangement with main effects being 2 MR (C4− vs. C4+) and 2 CS (BE− vs. BE+). The 4 individual treatments were (1) calves fed MR and CS without additives (control; C4−BE); (2) calves fed control MR with CS containing BE at 0.05% (496 mg/kg; C4−BE+); (3) calves fed MR with C4 added at 0.3% at feeding time with control CS (C4+BE−); and (4) calves fed MR with C4 and CS with BE added at same the inclusion rates (C4+BE+). Calves were fed 2×/d at 0630 and 1800 h along with ad libitum CS and free choice water. The MR was fed at 0.55 (DM basis) kg/d for d 1 to 14, then increased to 0.82 kg/d for d 15 to 42, and feeding reduced to 0.415 kg/d fed 1×/d for d 42 to 49, with weaning occurring after the 49-d experimental period. Three calves were excluded from data analysis because 2 calves died and 1 was a statistical outlier. The MR × CS interaction was nonsignificant for BW, BW gain, ADG, CS intake, and total DMI. The main MR effect demonstrated calves fed C4+ having greater BW (54.7 and 56.2 kg, for C4− and C4+, respectively), BW gain (29.0 and 31.7 kg), and ADG (591 and 648 g/d), but similar DMI (0.96 and 0.96 kg/d) compared with calves fed C4−. The number of days required for calves to consume 0.9 kg/d CS for 3 consecutive days (47.3 and 45.7 d) as a weaning criterion was lower (P < 0.05) for calves fed C4+ compared with calves fed C4−. The main CS effects for calves fed without or with BE were similar in BW, BW gain, ADG, CS intake, and total DMI. The overall study (0–49 d) feed conversion demonstrated a MR × CS interaction, with calves fed C4−BE− and C4+BE+ being greater than calves fed C4−BE+ with calves fed C4+BE− being intermediate and similar. The MR × CS interaction was nonsignificant for frame measurements, frame measurement gains, and fecal, nasal, and eye and ear scores, and similar for MR or CS main effects when fed without or with C4 and BE. Feeding neonatal calves C4 in the MR improved growth performance by reducing the days to achieve the weaning criteria. The feeding of a BE did not improve growth performance and did not improve growth performance in the presence of C4.